A Review on Application of Poly(3,4-ethylenedioxythiophene) (PEDOT) in Rechargeable Batteries - Laisuo Su; Shwetha Sunil Kumar; Arumugam Manthiram; B. Reeja-Jayan (Organic Materials, 2022)
Abstract Since the very first patent on poly(3,4-ethylenedioxythiophene) (PEDOT) that was filed in 1988, this polymer has been widely utilized and has achieved great success owing to its high electrical conductivity and excellent stability. The application of the conducting polymer, PEDOT, in renewable energy devices, especially rechargeable batteries, is attracting increasing attention due to its potential to solve the energy and climate crisis. In this review, we summarize the research over the past few decades directed toward the application of PEDOT in rechargeable batteries aimed at improving their electrochemical performance. We focus on PEDOT synthesized via oxidative chemical vapor deposition (oCVD), a relatively new process known for its ability to grow conducting polymer thin films with uniform, pinhole-free properties, and controllable thickness and conformality. For a comparison purpose, PEDOT synthesized via solution-based methods is also briefly summarized. Finally, future research directions for applying oCVD PEDOT in rechargeable batteries are discussed. Introduction PEDOT Synthesis Methods Application of oCVD PEDOT in Rechargeable Batteries Applications of Solution-Based PEDOT in Rechargeable Batteries Conclusions and Outlook